Towards an understanding of ekphrasis: Morten Søndergaard’s Nedtcelling til en skulptur af Michelangelo (Pieta di Rondamni i Milano) - Mrozewicz, Anna (Folia Scandinavica Posnaniensia, 2007)
Morten Søndergaard is one of the best known Danish poets who made their debut in the nineties. The visual arts as well as the tension between language and the reality to which words are supposed to refer play a remarkable role in the poet’s oeuvre. Hie article investigates the problem of poetic language in an encounter with a sculpture. The first part introduces some issues o f ekphrasis, which serve as a point of departure for an analysis of S0ndergaard’s poem. TTie aim of the analysis is an examination of a paradox central to the meaning of the poem: while undermining the possibility of verbal representation, the poem introduces various strategies attempting to imitate sculpture. The poet’s struggle with language becomes simultaneously the reader's, who faces the question of how to “find our way through what separates words from what is both without a name and more than a name: a sculpture.”1